STRATEGI PENINGKATAN KUALITAS PELAYANAN UNTUK KEPUASAN PELANGGAN DENGAN INTEGRASI METODE SERVQUAL, QFD DAN TOPSIS - Fulvian Rokhman Hakim; Wiwik Sulistiyowati (Industrika : Jurnal Ilmiah Teknik Industri, 2022)
Minimarket "X" is a business engaged in retail sales of daily necessities. In providing services there are complaints that occur in October of 11.06%, November of 12.52% and December of 13.27% in 2021. Complaints that make customers feel dissatisfied are price suitability, availability of empty products, price tag, parking space and employee friendliness. The purpose of this study is to make customers feel satisfied when shopping by improving service quality. In this study using the SERVQUAL method of calculation to determine the level of customer satisfaction and gap problems that occur. The QFD method is used in planning, service development and evaluating service performance as well as integrating with the TOPSIS method to rank each alternative solution. Based on the results of research conducted from the SERVQUAL method, there are 9 service attributes from Minimarket "X" that have met customer expectations and 21 service attributes require improvement. So that the improvement of service quality using the QFD method obtained 11 technical responses for improvement and using the TOPSIS method, priority was obtained on the technical response that would be used as a policy in developing services by taking into account 5 criteria, namely, budget (C1), policy suitability with customer needs (C2), accessibility of implementation policy (C3), enthusiasm in policy implementation (C4), capability towards policy implementation (C5). So that the results of the integration of service quality improvement indicate the priority of service policies that must be carried out first, namely the policy of providing services in accordance with procedures. Keywords: Service, Satisfaction, SERVQUAL, QFD, TOPSIS